The curse that plagues the content of Africa: in-depth analysis of the resource curse and policy recommendations to avoid it - Feldman, Zac (My University, 2020)
The resource curse is a phenomenon that is both paradoxical and controversial. It is argued that the curse both exists and is a construct of western discrimination. The resource curse as coined first by Auty (1993) claims that an increase in natural resource growth will cause a decrease in domestic growth should certain factors exist. This paper examines the nature of the curse and empirically demonstrates the true nature of this occurrence. Furthermore, this paper engages with some of the factors that cause this curse to rear its head. It proposes policy recommendations that will help nations create GDP growth when faced with increasing resources and avoid some of the pitfalls other economies have suffered. The first section of this paper tests the existence of the resource curse empirically using Sachs and Warner(Warner, 1997), Gylfason (2001) and Manzano and Rigabon (2001). We prove the existence of the curse in African developing countries and show the severity of the curse. Moreover, the section assesses the severity of the curse in each economy and provides indications as to how drastic the presence of the curse is. Moreover, section two of the paper examines some of the root causes of the resource curse. We examine the resource pull effect, degrading of human capital as well as lack of savings. We test these results empirically using Mehlum Moene Torvik (2006), Oskenbayev et al (2013) and Gylfason and Zoega (2004). Furthermore, we construct an optimum model that both diagnoses the resource curse as well as indicates some of the potential causes in the given economy. We provide some Policy recommendations that can be taken in order to avoid some of these causes
A research report submitted in fulfilment of the requirements for a degree of Masters in Commerce, at the University of Witwatersrand, Johannesburg, Faculty of Commerce, Law and Management, 2020
Keywords: Resource curse; Economic development--Africa; Natural resources--Africa